The birth of a healthy child in the assisted reproductive technologies program after autologous co-culture of embryo with cumulus cells and a new CAT transfer technology. Case report - Gunai R. Asfarova; Veronika I. Smol'nikova; Natalia P. Makarova; Iuliia S. Drapkina; Anastasiia P. Sysoeva; Nataliia N. Lobanova; Elena A. Kalinina (IP Berlin A.V., 2021)
Cumulus cells are essential during oocytes growth and development, as well as during their maturation and fertilization. Research results have shown that embryo co-cultivation with autologous cumulus cells increases the frequency of blastocyst formation, and also improves the effectiveness of ART programs. Embryo transfer in such programs is recommended to be carried out using the CAT technology (Cumulus-Aided embryo Transfer), which includes embryo cultivation on a layer of cumulus cells and embryo transfer with a certain amount of diluted cumulus cells. Patient G., 38 years old, came to the department with infertility for 15 years and recurrent implantation failure in history. The patient had ART program with autologous co-cultivation of embryos with cumulus cells and a new CAT transfer technology. The patient fell pregnant and gave birth to a healthy child. Autologous cumulus cells can be a source of biologically active substances and improve embryological parameters and implantation rate in ART programs. Embryo co-cultivation with cumulus cells is especially important for patients with recurrent implantation failure. This technique can become an alternative for optimizing human embryos culturing.